LEGALISASI PENCABUTAN HAK POLITIK TERPIDANA TINDAK PIDANA KORUPSI UNTUK SELAMANYA - Tomson Situmeang (Fakultas Hukum Universitas Kristen Indonesia, 2017)
Abstract The country will progress if it successfully carries out the development of 2 (two) main factors, namely: â€œnatural resourcesâ€ and â€œhuman resourcesâ€. Indonesia, with its abundant natural resources, is not even among the 10 (ten) highest income countries in Asia. This is due to the corrupt behavior of officials (state) in Indonesia by abusing the position or position obtained, one of them through the political process. Such people are no longer fit to return to political office, so their political rights must be revoked. Revocation of political rights is indeed accepted and recognized in Indonesian law, namely in the provisions of Article 28J of the 1945 Constitution and Article 73 of the Human Rights Law which mandates limitations to the provisions of the law. In addition, there are provisions in Article 10 of the Criminal Code jo. Article 35 of the Criminal Code jo. Article 38 of the Criminal Code jo. Article 18 Corruption Law can be carried out by a judgeâ€™s decision. Therefore, revocation of the political rights of convicts of criminal acts of corruption can be done forever, provided that they are stipulated in the provisions of the law by including corruption in the category of disgraceful acts. Keywords: pencabutan hak politik, tindak pidana korupsi, perbuatan tercela